2015
DOI: 10.1158/1055-9965.epi-15-0199
|View full text |Cite
|
Sign up to set email alerts
|

Gallbladder Cancer Incidence and Mortality, United States 1999–2011

Abstract: Background: Gallbladder cancer is a rare cancer with unusual distribution, and few population-based estimates for the United States have been published.Methods: Using population-based cancer incidence and mortality data, we examined U.S. gallbladder cancer incidence and death rates for 2007-2011 and trends for 1999-2011.Results: During 2007 to 2011, approximately 3,700 persons were diagnosed with primary gallbladder cancer (rate ¼ 1.13 cases per 100,000) and 2,000 died from the disease (rate ¼ 0.62 deaths per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
76
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(89 citation statements)
references
References 21 publications
6
76
0
Order By: Relevance
“…In agreement with prior studies, we found that GBC incidence rates were highest among women, Hispanics, and older age groups . These differences between demographic groups in GBC incidence rates may be explained by variations in risk factor prevalence by sex and race/ethnicity.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with prior studies, we found that GBC incidence rates were highest among women, Hispanics, and older age groups . These differences between demographic groups in GBC incidence rates may be explained by variations in risk factor prevalence by sex and race/ethnicity.…”
Section: Discussionsupporting
confidence: 92%
“…Overall, GBC incidence rates declined, but trends differed by demographics. Although the incidence declined among females, rates remained stable among males .…”
Section: Discussionmentioning
confidence: 95%
“…In 2018, an estimated 1000 Hispanic women will be diagnosed with gallbladder cancer. Hispanic women in the United States have the second highest incidence and mortality rates after American Indian/Alaska Native women . The incidence rate in Hispanic women (2.5 per 100,000) is double that of Hispanic men (1.2 per 100,000) and NHW women (1.1 per 100,000) and triple that of NHW men (0.7 per 100,000) (Table ).…”
Section: Selected Findingsmentioning
confidence: 99%
“…Information regarding gallbladder cancer in the scientific literature is scant due to its rarity, particularly in economically developed countries. In the United States, Hispanic women have the second highest incidence and mortality rates after American Indian/Alaska Native women . The incidence rate in Hispanic women (2.6 per 100,000 population) is double that of Hispanic men (1.2) and NHW women (1.1) and triple that of NHW men (0.7) (Table ).…”
Section: Selected Findingsmentioning
confidence: 99%